7 Habits of Highly Effective Families : Building a Beautiful Family Culture in a Turbulent World - Stephen R Covey (Simon & Schuster, 1977)
The bestselling book that offers precious lessons in creating and sustaining a strong family culture in a turbulent world.No family is free from challenges from its own members or from the outside world. Now, with the same profound insight, simplicity and practical wisdom that propelled THE 7 HABITS OF HIGHLY EFFECTIVE PEOPLE to worldwide acclaim, Stephen R. Covey focuses on the primary concern of society today - the family. Using the 7 Habits Covey creates a powerful framework of timeless, universal and self-evident principles that enable family members to communicate effectively about their problems and resolve them. He also shows how families can move from a problem-solving to a creative mind-set, focusing on accomplishing goals and contributing together in meaningful ways.